Peningkatan Keterampilan Membaca Pemahaman Proses Membaca dalam Pembelajaran Tematik Terpadu di Kelas IV SD - Ria Angelina Hutauruk; Taufina Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this study is to describe the increased reading skills of understanding by the process of reading skills in Class IV SD Rujukan 04 Birugo Kota Bukittinggi. This type of research is Classroom Action Research using qualitative and quantitative approaches. The subjects of the research were teacher and 23 class IV students.  The results of the study indicate an increase in the implementation and student learning outcomes. The results of lesson plan observation on cycle I was 81.94%, and cycle II was 94.44%. Assessment of the implementation of teacher activities in the first cycle averaged 81.25%, in the second cycle an average of 94.44%. Assessment of the implementation of student activities in the first cycle averaged 77,08%, in the second cycle an average of 91.33%. The results of the recapitulation of student scores in the first cycle with a class average of 72.69%, in the second cycle the results of the recapitulation were 90,41%, , and in the skill aspect it gets an average of 81,45 to 88.02.